Life after meiosis: patterning the angiosperm male gametophyte. (22nd March 2010) - Borg, Michael; Twell, David
Abstract : Pollen grains represent the highly reduced haploid male gametophyte generation in angiosperms. They play an essential role in plant fertility by generating and delivering twin sperm cells to the embryo sac to undergo double fertilization. The functional specialization of the male gametophyte and double fertilization are considered to be key innovations in the evolutionary success of angiosperms. The haploid nature of the male gametophyte and its highly tractable ontogeny makes it an attractive system to study many fundamental biological processes, such as cell fate determination, cell-cycle progression and gene regulation. The present mini-review encompasses key advances in our understanding of the molecular mechanisms controlling male gametophyte patterning in angiosperms. A brief overview of male gametophyte development is presented, followed by a discussion of the genes required at landmark events of male gametogenesis. The value of the male gametophyte as an experimental system to study the interplay between cell fate determination and cell-cycle progression is also discussed and exemplified with an emerging model outlining the regulatory networks that distinguish the fate of the male germline from its sister vegetative cell. We conclude with a perspective of the impact emerging data will have on future research strategies and how they will develop further our understanding of male gametogenesis and plant development.